2005
DOI: 10.1080/09593960500119416
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Productivity of the UK Retail Sector

Abstract: ABSTRACT:Several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 27 publications
0
59
0
2
Order By: Relevance
“…The choice of productivity measure really matters in hospitality as in other service sectors (Reardon and Vida 1998). Market imperfections are usually considered important in explaining differences between physical and financial productivity (Reynolds et al 2005) in the generic literature, as are differences between new entrants and existing firms, but neither explanation would apply in a clear and consistent way across departments within a single firm. The differences between departments reinforce Brown and Dev's (2000) conclusion that firm or even establishment-level estimates of hotel productivity, can conceal major differences in departmental performances (Baker and Riley 1994).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of productivity measure really matters in hospitality as in other service sectors (Reardon and Vida 1998). Market imperfections are usually considered important in explaining differences between physical and financial productivity (Reynolds et al 2005) in the generic literature, as are differences between new entrants and existing firms, but neither explanation would apply in a clear and consistent way across departments within a single firm. The differences between departments reinforce Brown and Dev's (2000) conclusion that firm or even establishment-level estimates of hotel productivity, can conceal major differences in departmental performances (Baker and Riley 1994).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This is a recurring theme in the general literature on productivity (Bloom and van Reenen 2010;Faggio, Salvanes, and van Reenen 2007), stemming from concerns about the limitations of findings derived from aggregated metrics (Reynolds et al 2005), due to aggregation bias or loss of variation (Higon et al 2010). Research on hotels similarly found that aggregated productivity metrics obscured the performances of different departments (Brown and Dev 2000), which conceivably can operate in contrasting directions (Baker and Riley 1994), not least because there tend to be important differences in operating conditions at this scale.…”
Section: Productivity In the Service Sector: Partial Measures And Hetmentioning
confidence: 99%
See 1 more Smart Citation
“…The retail sector in particular has been identified as one of the biggest contributors to the productivity gap that persists between the UK, other European countries and the USA [2].…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that management practices are linked to the performance of an organisation (Reynolds et al, 2005;Wall & Wood, 2005). Best practices have been developed, but when it comes down to the actual application of these guidelines considerable ambiguity remains regarding their effectiveness within particular contexts (Siebers et al, forthcoming a).…”
Section: Introductionmentioning
confidence: 99%